Adjustable sensitivity for hydrogen gas sensing using perpendicular-to-plane ferromagnetic resonance in Pd/Co Bi-layer films. (2nd February 2017) - Lueng, Chris; Metaxas, Peter J.; Sushruth, Manu; Kostylev, Mikhail
Abstract: In this work we measure hydrogen gas concentration using ferromagnetic resonance in a Pd/Co bi-layer film. The gas detection method is based on a previously demonstrated ferromagnetic resonance (FMR) peak shift which occurs in the presence of hydrogen. We find however that the maximum range of hydrogen concentrations which can normally be measured using this approach is smaller than the whole potential concentration range (i.e. 0%–100%); with the width of the accessible range being dictated by the width of the ferromagnetic resonance line. However, we demonstrate that this challenge can be addressed by exploiting the fact that the FMR peak position depends on the magnetic field applied to the sample. We show that by properly adjusting the magnetic field, overlapping sub-ranges covering a very wide range of hydrogen gas concentrations, from 0.2% to 100%, can been accessed. We speculate that a real-world broad-range device will be composed from 3 to 4 sensors, each of them tuned to a particular sub-range of concentrations and that shape-anisotropy bias can be used instead of applying external magnetic fields to the sensors. Highlights: Sensitivity of ferromagnetic resonance in Pd/Co films to H2 was measured. This was demonstrated over a large range of H2 concentrations – 0.2%–100%. A careful choice of the magnetic bias field optimises the sensitivity. Concentration resolution decreases when increasing the H2 concentration. However, it remains significant when approaching 100% H2 .